New graphene-CoxZn1−xFe2O4 nano-heterostructures: Magnetically separable visible light photocatalytic materials. Issue 6 (1st May 2016) - Nazim, Sidra; Kousar, Tehmina; Shahid, Muhammad; Khan, Muhammad Azhar; Nasar, Gulfam; Sher, Muhammad; Warsi, Muhammad Farooq
Abstract: Magnetic Co x Zn1− x Fe2 O4 nanoparticles and Co x Zn1− x Fe2 O4 -graphene nano-heterostructures were prepared by chemical co-precipitation route and ultra-sonication method respectively. The characterization of Co x Zn1− x Fe2 O4 nanoparticles was carried out by thermo-gravimetric analysis (TGA), X-ray powder diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), scanning electron microscopy, vibrating sample magnetometry (VSM). TGA predicted the phase formation temperature around 850 °C. XRD and FTIR confirmed the single phase cubic structure. Crystallite size as calculated by Scherrer׳s formula was found 50–70 nm; however the nanoparticles size determined by TEM was found 35–75 nm. VSM confirmed the ferromagnetic nature of both ZnFe2 O4 and Co0.3 Zn0.7 Fe2 O4 nanoparticles. The reduced graphene oxide (rGO) prepared by modified Hummer׳s method was characterized by UV–visible (UV–vis) spectroscopy and XRD. As prepared rGO was utilized for preparation of Co x Zn1− x Fe2 O4 -rGO nano-heterostructures. SEM confirmed the well dispersed Co x Zn1− x Fe2 O4 nanoparticles among rGO sheets. Electrochemical impedance spectroscopy (EIS) studies of Co x Zn1− x Fe2 O4 nanoparticles and their nano-heterostructures with rGO showed that Co x Zn1− x Fe2 O4 nanoparticles exhibit the high charge transfer resistance as compared to nano-heterostructures. The photocatalytic efficiency of Co x Zn1− x Fe2 O4 nanoparticles and their nanocomposites with rGO was evaluated using methylene blue as model organic compound in the presence of visible light. The Co x Zn1− x Fe2 O4 -rGO nano-heterostructures showed more efficiency as compared to Co x Zn1− x Fe2 O4 nanoparticles. The ferrite nanoparticles and their nano-heterostructures with rGO could be separated and recycled by conventional magnetic bars easily.